Intraoperative Cardiac Arrest: An Algorithm to Address the Synchronous Underlying Pathology - Mahmood, Ali; Yaakovian, Michael; Ellis, Byron Keith; Nazareth, Karl; Patel, Apoor; Mahmood, Aiva Mariam; Mahmood, Emaan Anya; Mock, Emily (British Journal of Healthcare and Medical Research, 2024)
Intra-operative cardiac arrest (IOCA) is a rare yet feared complication. It has been reported with diverse range: from 0.8/10,000 cases to 21/100,000 cases. [1,2,3] The immediate mortality and subsequent 30 days mortality are paramount, from 62% to 75%, respectively. [1,2] Patients that had incurred an operation due to trauma had an even worse prognosis, in some studies. [4] Elective cases, where the arrest was addressed with a resuscitation algorithm, unobstructed communication, and teamwork between the surgery and anesthesia teams, fared the most favorable outcomes. [5] Some literature has even reported that the use of CPR, when necessary, was a poorer prognostic indicator. [6] Often successful resuscitation and rescue of the patient from IOCA is performed before the surgeon has had the opportunity to address the pathology that originally scheduled the patient for an operation. There is not an established algorithm of how or when to take the patient back to the operating room to address the underlying pathology. We propose an algorithm where a successfully resuscitated patient, without sustaining a myocardial infarction (MI), can be appropriately worked up, managed, undergo prophylactic cardiac protection, and return to the operating room for a successful operation.